Diversity And Distribution Of Benthic Foraminifera In Mangrove Forests Of Penang Island - Malek, Muhamad Naim Abd (2023)
Foraminifera is one of the diverse groups of organisms inhabiting mangrove environment, but local studies regarding benthic foraminifera are limited. Therefore, this study was conducted to examine the diversity and distribution patterns of the foraminifera species in mangrove forests around Penang Island, which were Teluk Tempoyak, Pulau Betong, and Kuala Sungai Pinang. A total of 648 surface sediment samples (N=18 points × 3 mangrove forests × 12 months) of 1 cm thick were randomly collected using scoops during the lowest spring tide. The sampling was conducted monthly from March 2017 to February 2018. The results showed low to moderate species diversity (H’ index: 0-1.4), typical of a mangrove environment. Overall, 29 benthic foraminifera species were identified, predominantly agglutinated with some combination of hyaline and porcelaneous tests. Benthic foraminifera in Pulau Betong mangrove recorded the highest species diversity (29 species), followed by Teluk Tempoyak (25 species) and Kuala Sungai Pinang (19 species). The species idetified are commonly found in mangrove swamps and in the coastal environment. Species distribution demonstrated significant variation among the different locations, zones, and seasonal factors in the three mangrove forests (p < 0.05).